Search for Higgs boson pair production in the γγWW∗ channel using pp collision data recorded at √s = 13 TeV with the ATLAS detector - Santos, S. P. Amor dos (2018)
Searches for non-resonant and resonant Higgs boson pair production are performed in the γγWW∗ channel with the final state of γγ νj j using 36.1 fb−1 of proton– p√roton collision data recorded at a centre-of-mass energy of s =13 TeV by the ATLAS detector at the Large Hadron Collider. No significant deviation from the Standard Model prediction is observed. A 95% confidence-level observed upper limit of 7.7 pb is set on the cross section for nonresonant production, while the expected limit is 5.4 pb. A search for a narrow-width resonance X decaying to a pair of Standard Model Higgs bosons HH is performed with the same set of data, and the observed upper limits on σ(pp → X) × B(X → HH) range between 40.0 and 6.1 pb for masses of the resonance between 260 and 500GeV, while the expected limits range between 17.6 and 4.4 pb. When deriving the limits above, the StandardModel branching ratios of the H→γγ and H→WW∗ are assumed.